Omega-3 Fatty Acids and Health. A Literature Review - Machaj, Damian; Stawińska-Dudek, Julia; Józefowicz, Wiktoria; Brzoza, Martyna (Quality in Sport, 2025)
Introduction and Purpose: Omega-3 polyunsaturated fatty acids (PUFAs) are essential nutrients primarily obtained from marine sources. These compounds, particularly EPA (eicosapentaenoic acid) and DHA (docosahexaenoic acid), play a critical role in modulating inflammation, supporting cardiovascular and neurological health, and potentially preventing certain cancers. Despite extensive research, mixed clinical results highlight the need for comprehensive analyses. This study aims to synthesize findings on omega-3’s effects on cardiovascular health, neurocognitive development, inflammation, and bioavailability challenges, with a particular focus on research published between 2012 and 2024. Methodology: The review is based on the thorough analysis of the materials selected from “PubMed” and “Google Scholar” scientific databases from 2012 to 2024 using the following key words: dietary supplements, DHA, EPA, omega-3 fatty acids. These key words were chosen based on their relevance to the matter of an article. Conclusions: Omega-3 fatty acids demonstrate notable benefits in reducing inflammation, improving lipid profiles, enhancing cognitive function, and lowering the risk of cardiovascular events. However, results regarding the efficacy of omega 3 in the prevention and treatment of chronic disease are inconsistent, due to differences in dosage, bioavailability and study design.